Hubungan Infestasi Ctenocephalides felis dan Xenopsylla cheopis dengan Perawatan Kucing Rumah (Felis catus) di Kabupaten Banjarnegara - Eva Lestari; Rahmawati Rahmawati; Dewi Puspita Ningsih (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2020)
Fleas as ectoparasites live on the cat's body surface. Ctenocephalides felis is one of the type fleas that often found in cats. The presence of fleas in cats can be influenced by the way the cat is groomed. Fleas in cats have the potential to transmit the disease to a human. The purpose of this study was to determine fleas infestation in domestic cats and determine factors that affect the presence of fleas in cats. This study was observational analytic with a cross-sectional approach and conducted in Banjarnegara Regency on June-November 2019. Total of 100 domestic cats (Felis catus) were checked for fleas. Interviews were conducted with cat owners to obtain information on how to groom cats. Data were analyzed descriptively and statistically using Mann-Whitney and Chi-Square Test. The results showed a greater percentage of fleas positive in groomed cats (82%) than ungroomed cats (68%). Fleas species found in cats were C. felis (99.8%) and Xenopsylla cheopis (0.2%). Based on statistical analysis there was no difference amount of fleas between groomed cats and ungroomed (p = 0.072). A correlation test showed a relationship between the frequency of cats being bathed with cat-specific shampoo and the presence of fleas in cats (p = 0.001). While the habits of cats caging (p = 0.331), the supply of ectoparasiticides (p = 0.177), and the number of cats kept (p = 0.884) showed no significant relationship with the presence of fleas in cats.